2016
DOI: 10.1590/0074-02760150390
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of entecavir and tenofovir in chronic hepatitis B under treatment in the public health system in southern Brazil

Abstract: There are about 350 million hepatitis B virus (HBV) carriers worldwide and chronic HBV is considered a major public health problem. The objective of the present study was to assess the effectiveness of the nucleos(t)ide analogues tenofovir (TDF) and entecavir (ETV) in the treatment of chronic HBV. A cross-sectional study was carried out from March-December 2013, including all patients with chronic HBV, over 18 years of age, undergoing therapy through the public health system in southern Brazil. Only the data r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…In North America, Morris and his colleagues from Toronto-Canada, found in his study of (HBeAg)-positive, Lamivudine refractory patients that switching to Entecavir was superior to continued Lamivudine at week 48 it regards to histological improvement, viral load reduction, and ALT normalization [24]. Results from South America are also comparable to our data regarding efficacy and safety of entecavir [25,26]. However, a similar but smaller study from Morocco, North Africa showed only 85% viral response in 48 weeks follow up of 41 patients on Entecavir therapy [27].…”
Section: Discussionsupporting
confidence: 85%
“…In North America, Morris and his colleagues from Toronto-Canada, found in his study of (HBeAg)-positive, Lamivudine refractory patients that switching to Entecavir was superior to continued Lamivudine at week 48 it regards to histological improvement, viral load reduction, and ALT normalization [24]. Results from South America are also comparable to our data regarding efficacy and safety of entecavir [25,26]. However, a similar but smaller study from Morocco, North Africa showed only 85% viral response in 48 weeks follow up of 41 patients on Entecavir therapy [27].…”
Section: Discussionsupporting
confidence: 85%
“…Among these selected studies, 17 focused on the comparison of TDF vs. ETV, 5 focused on the comparison of TAF vs. TDF, and 6 focused on the comparison of TDF+ETV vs. TDF. Among these selected studies, 13 were RCTs, 15 27 14 were cohort studies, 28 41 and only 1 was a cross-sectional study 42 ( Table 1 ). Quality assessment suggested that all the cohort studies and RCTs possessed high quality ( Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This proportion increases to 100% in both groups at month 18. In other studies conducted in real clinical practice with chronic hepatitis B patients, overall viral load negativization rates at 12 months in patients treated with tenofovir ranged from 59.2 to 91.9% [ 24 , 25 , 47 , 49 51 ]; and with entecavir, from 41 to 89.4% [ 21 23 , 51 – 62 ]. These differences between the studies are possibly due to the diverse populations studied in each case, the different sensitivity of the PCR used to detect viral load, and to the fact that, in many studies, patients previously treated with other treatments for HBV are included.…”
Section: Discussionmentioning
confidence: 99%